The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12913-019-4427-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of dental visits among older adults: findings of a nationally representative longitudinal study

Abstract: Background The first aim was to present descriptive data on the frequency of dental visits among older adults in Germany. The second aim was to identify the determinants of the number of dental visits using a longitudinal approach. Methods Longitudinal data were derived from the German Ageing Survey, which is a nationally representative sample of community-dwelling individuals ≥40 years in Germany. The frequency of dental visits in the past 12 months was recorded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
(33 reference statements)
1
30
0
3
Order By: Relevance
“…A number of studies found that women use (mainly outpatient) healthcare more frequently than men, largely due to a difference in general health status [ 25 , 26 ]. It has also been found that women have better oral health and lower treatment needs than men [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found that women use (mainly outpatient) healthcare more frequently than men, largely due to a difference in general health status [ 25 , 26 ]. It has also been found that women have better oral health and lower treatment needs than men [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two trends, frequency of regular dental visits (previous research) on the one hand [ 1 , 4 , 13 ], and avoidance of needed treatment (present study) on the other, might run reversely with rising age. This observation is supported by results of another large population-based study, which detected that younger adults within the older age group (≥ 50 years) are more likely to postpone their dental visits due to financial reasons [ 20 ].…”
Section: Discussionmentioning
confidence: 44%
“…Since the here presented data of the DEAS study was collected, no other German (and global) studies were published that focused on the determinants of dental treatment avoidance in particular. But in previous data, it has already been demonstrated that the frequency of dental visits decreases with increasing age [ 1 , 4 , 13 ]. The results of the presented study show that, within this age group of older adults (≥ 40 years), younger adults are more likely to avoid dental treatment than older adults, despite being aware of their treatment need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that OHSU was low in older adults. It has been reported that OHSU diminishes with age [ 22 ]. This could be attributed to the consequences of aging-related difficulties in communicating and functional dependence [ 23 , 24 ], which may compromise older adults’ social skills and mobility and may alter their patterns of healthcare utilization.…”
Section: Discussionmentioning
confidence: 99%